2011
DOI: 10.1371/journal.pone.0014542
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Reduces Insulin-Resistance in Human Endothelial Cells

Abstract: BackgroundThe efficacy of Phosphodiesterase 5 (PDE5) inhibitors to re-establish endothelial function is reduced in diabetic patients. Recent evidences suggest that therapy with PDE5 inhibitors, i.e. sildenafil, may increase the expression of nitric oxide synthase (NOS) proteins in the heart and cardiomyocytes. In this study we analyzed the effect of sildenafil on endothelial cells in insulin resistance conditions in vitro.Methodology/Principal FindingsHuman umbilical vein endothelial cells (HUVECs) were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 37 publications
(41 reference statements)
4
37
0
1
Order By: Relevance
“…22 Lastly, sildenafil has been shown to cause vessel dilation by inhibiting cGMP-specific phosphodiesterase type 5, which degrades cGMP and hence results in elevated level of cGMP that leads to smooth muscle relaxation, thus its effects on vessel relaxation were not expected to be endothelial specific. 23 However, in a recent study, sildenafil was also reported to increase expression of nitric oxide synthase in human endothelial cells 24 motivating the study of sildenafil here.…”
Section: Drug Induced Nitric Oxide Secretion and Monocyte Adhesionmentioning
confidence: 89%
“…22 Lastly, sildenafil has been shown to cause vessel dilation by inhibiting cGMP-specific phosphodiesterase type 5, which degrades cGMP and hence results in elevated level of cGMP that leads to smooth muscle relaxation, thus its effects on vessel relaxation were not expected to be endothelial specific. 23 However, in a recent study, sildenafil was also reported to increase expression of nitric oxide synthase in human endothelial cells 24 motivating the study of sildenafil here.…”
Section: Drug Induced Nitric Oxide Secretion and Monocyte Adhesionmentioning
confidence: 89%
“…Although the precise mechanism of HbA 1c reduction upon inhibition of PDE5 is unclear, preclinical and clinical studies suggest that PDE5 inhibition may favorably impact glucose metabolism in T2DM by mediating enhanced glucose uptake in skeletal muscle 22,23 improving b-cell function and decreasing insulin resistance. [24][25][26] Such mechanisms may eventually contribute to the improvement in microvascular disease and subsequent reduction of albuminuria in studies of longer treatment duration with PF-0048971. In addition, a large set of preclinical studies conducted in animal models of diabetic and nondiabetic kidney disease have demonstrated the beneficial effect of PDE5 inhibition on pathophysiological pathways implicated in albuminuria, glomerulosclerosis, and tubulointerstitial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hyperinsulinemia during IR can cause vascular disease by promoting synthesis of lipophilic analogs and stimulating the proliferation of smooth muscle cells of the vessel endangium (19). Indeed, high levels of insulin can stimulate synthesis and release of endothelin (ET-1) from endothelial cells, and ET-1 can combine with the endothelin receptor in smooth muscle cells of the endangium to produce strong vasoconstriction (20).…”
Section: Discussionmentioning
confidence: 99%